Radiative Lifetime, Non‐Radiative Relaxation, and Sensitization Efficiency in Luminescent Europium and Neodymium Cryptates – The Roles of 2, 2′‐Bipyridine‐N, N′‐dioxide and Deuteration. Issue 17 (29th July 2019) - Trautnitz, Markus F. K.; Doffek, Christine; Seitz, Michael
Abstract: Five luminescent tris(bipyridine)‐based cryptates with the lanthanoids Eu and Nd have been prepared with a systematic increase in the number of 2, 2′‐bipyridine‐ N, N′ ‐dioxide units and with different deuteration levels in the complexing cryptands for the europium species. Careful analysis of the radiative lifetime τrad in these systems reveals that an increase in N ‐oxide units around the metal centers uniformly lowers τrad by about 30–40 %. The potential involvement of nephelauxetic effects is discussed. Exchange of 30 C−D for C−H oscillators around the europium centers does not affect the radiative lifetimes but decreases non‐radiative deactivation and increases the overall luminescence quantum yield in D2 O by 45 %. Abstract : 2, 2′‐Bipyridine‐ N, N′ ‐dioxide units are a tool for the synthetic design of lanthanoid complexes with low radiative lifetime (τrad ) values.